Pengaruh Penambahan Wortel (Daucus Carota L) dengan Bakteri Asam Laktat (BAL) Pediococcus Pentosaceus dalam Pakan terhadap Kualitas Karkas Ayam Pedaging - Haryadi Haryadi; Muhammad Firdaus; Asmaul Husna (Pusat riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of giving carrots (Daucus Carota L) with lactic acid bacteria (LAB) pediococcus pentosaceus in feed on broiler chicken carcass quality. The research used is a field experiment using a Completely Randomized Design (CRD) and if there is a significant difference in effect then it will be continued with the Duncan test. The treatments used in this research were 4 treatments with 3 repetitions so there were 24 experimental units. The results showed that the addition of carrots up to 3% with 1 ml of pediococcus pentosaceus lactic acid bacteria could not increase carcass percentage, breast meat deposition and abdominal fat percentage.